A Critique for the Book of "The Future of Power" The Future of Power or the Future of the United States of America? - Hakem Ghasemi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
"The Future of Power", by Joseph Nye, exploring international developments, explains the types of power, and while considering the conditions that make effective the use of different types of power, it also explains their limitations. In this book, after examining the types of power, the status of American power is evaluated and its weaknesses are mentioned. The author does not consider the use of any kind of power to be effective for preserving American power, and introduces the integrating of all different types and sources of power as the only way to make them effective. Nye presents a strategy of smart power to maintain America's supremacy in the world and invites US politicians to comply. This book is extremely American-centered and is about a powerful future country, rather than about the future of power and its nature. This feature turns the book into a set of political guidelines for American politicians to preserve America's global power and position, and reflects the author's political attitudes and aspirations that have profoundly influenced American politicians and policies, especially Democrats and their policies.